Pengembangan Permainan Mobile AR Fishing Berbasis Marker Menggunakan Metode Iterative And Rapid Prototyping - Yanitra Dwi Luthansyah; Wibisono Sukmo Wardhono; Adam Hendra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Fishing is an activity that has been existed and done by humans since 100,000 years ago. Fishing activities that were initially done to survive by searching for fish to consume are now evolving into a favorite hobby of many people. Games can be used to simulate fishing as a hobby. The use of augmented reality technology can visualize realness in a fishing game. Gameplay is the most important part of a game. To design a gameplay from fishing game, the iterative and rapid prototyping method is required. The test results showed that the user response of the aspects of gameplay and the use of augmented reality in this game is good enough.